Proceedings of Ninth International Conference on Wireless Communication and Sensor Networks WCSN 2013 - Maringanti, Radhakrishna; Tiwari, Murlidhar; Arora, Anish (Lecture Notes in Electrical Engineering, 2014)
Wireless communication and sensor networks would form the backbone to create pervasive and ubiquitous environments that would have profound influence on the society and thus are important to the society. The wireless communication technologies and wireless sensor networks would encompass a wide range of domains such as HW devices such as motes, sensors and associated instrumentation, actuators, transmitters, receivers, antennas, etc., sensor network aspects such as topologies, routing algorithms, integration of heterogeneous network elements and topologies, designing RF devices and systems for energy efficiency and reliability etc. These sensor networks would provide opportunity to continuously and in a distributed manner monitor the environment and generate the necessary warnings and actions. However most of the developments have been demonstrated only in controlled and laboratory environments. So we are yet to see those powerful, ubiquitous applications for the benefit of the society. The conference and consequentially the proceedings would provide opportunity to the researchers to interact with other researchers and share their researches covering all the above areas. The proceedings of the conference thus covers the research work of different authors in the area of wireless sensor networks, wireless communications, devices, tools and techniques for WSN, and applications of wireless sensor networks. This book is beneficial for those researchers who are working in the area of wireless sensor networks, wireless communication, and developing applications of Wireless sensor networks.